Odpowiedź :
Odpowiedź:
[tex]\frac{6}{x+1}=4\\x\neq -1\\6=4(x+1)\\6=4x+4\\-4x=4-6\\-4x=-2\\x=\frac{1}{2}[/tex]
[tex]\frac{3x+2}{x}=5\\x\neq 0\\3x+2=5x\\3x-5x=-2\\-2x=-2\\x=1[/tex]
Szczegółowe wyjaśnienie:
Przykład A
***założenie: [tex]x+1\neq 0[/tex] --> x≠-1
[tex]\frac{6}{x+1}=4\\\\\frac{6}{x+1}=\frac{4(x+1)}{x+1}\\\\6=4(x+1)\\\\6=4x+4|-4\\\\6-4=4x\\\\2=4x|:4\\\\x=\frac{1}{2}[/tex]
Przykład B
***założenie x≠0
[tex]\frac{3x+2}{x}=5\\\\\frac{3x+2}{x}=\frac{5x}{x} \\\\3x+2=5x\\\\3x-5x=-2\\\\-2x=-2\\\\x=1[/tex]